The Relationship between Consumption Patterns of Macronutrients, Fiber, and Physical Activity with the Incidence of Obesity at Nuris Jember High School - Noveyani, Adistha Eka; Nurbaeti, Dini; Adi, Dhuha Itsnanisa (Utan Kayu Publishing, 2024)
Obesity is one of the global health problems whose incidence is expected to continue to increase every year. Obesity in adolescents is caused by many factors including changes in lifestyle, physical activity, diet with food intake that exceeds the body's needs, improper eating behavior by consuming more fast food, packaged food, and food with unbalanced nutrients. The purpose of this study was to determine the relationship between macronutrient diet, fiber, and physical activity with the incidence of obesity at Nuris Jember High School. This method is an observational study with a case-control design. Sample selection using purpose sampling of as many as 81 respondents consisting of 27 cases and 54 controls. The research instruments used were weight measurement, height, SQ-FFQ form, and PAL. Data were processed using statistical applications using the chi-square test and if not eligible, the Fisher's exact test was performed with a significant value of p less than 0.005. The results of macronutrient consumption patterns and physical activity have a significant relationship with the incidence of obesity (p less than 0.005). While the study could not analyze fiber consumption patterns due to homogeneous results, the existing findings provide a solid foundation for targeted nutrition education programs and public health strategies. This study concludes that there is a relationship between macronutrient consumption patterns and physical activity with the incidence of obesity. This conclusion underscores the importance of balanced diets and regular physical activity in preventing and managing obesity among adolescents.